Psychometric Properties of the Posttraumatic Stress Disorder Checklist among the Lebanese Population Exposed to the Beirut Explosion: A Cross-Sectional Study during the COVID-19 Pandemic - Fadwa Alhalaiqa; Othman A. Alfuqaha; Rami Masa’Deh; Anas H. Khalifeh; Mahmoud Alsaraireh; Natija S. Manaa; Osama Alkouri; Omar Al Omari (Behavioural Neurology)
Objective. This study was aimed at testing the psychometric properties of the posttraumatic stress disorder (PTSD) checklist for the Diagnostic Statistical Manual version 5 (DSM-5) (PCL-5) among the Lebanese population and at identifying the prevalence of PTSD. Design. A cross-sectional survey of PCL-5 among 950 Lebanese, using the online survey platform by Google Form, was conducted. Snowball recruitment was used to identify participants for the survey. Results. Face, content, construct, discriminant, and convergent validity had been accomplished through the survey. The reliability using Cronbach’s alpha, composite, and average variance extracted was identified as superior. We also found that more than half of the participants (55.6%) scored 33 or above which is the cut-off score for a likely diagnosis of PTSD. Conclusion. The current study provides further support for the validity and reliability of the Arabic version of PCL-5 among non-Western populations. This supports using the checklist in the screening of probable PTSD.